Estimates of genotypic and phenotypic variance, heritability, and genetic advance of horticultural traits in developed crosses of cowpea (Vigna unguiculata [L.] Walp) - Zaki, Haitham E. M.; Radwan, Khlode S. A. (Frontiers in Plant Science, 2022)
Cowpea, in addition to being a food and feed crop, plays a key role in sustainable farming. The present study’s goal is to develop new high-yielding cowpea varieties. A Field experiment was carried out across 3 summer seasons and the breeding program included 28 distinct cowpea varieties, out of which 5 potential parents were selected for this investigation. Local cultivars, i.e., Cream 7 ‘Cr7’, Dokki 331 ‘D331’, Commercial 1 ‘Com1’, and introduced cultivars, i.e., Colossus ‘Col’ and Asian Introduction ‘AI’ were utilized to produce six crosses in two generations apart; F1 and F2: Col x AI, Col x Com1, Cr7 x AI, Cr7 x Com1, D331 x AI, and D331 x Com1. ‘AI’ and ‘Com1’ were superior in pod length, pod diameter, number of seeds/pod and seeds weight/pod, whereas ‘Col’, ‘Cr7’ and ‘D331’ were superior in seeds yield/plant, number of pods/plant and the least number of aborted ovules/pod. The genotypes/crosses showed greater genotypic variance (GV) than phenotypic variance (PV) for number of pods/plant, pod length, number of seeds/pod, number of aborted ovules/pod, fresh pod weight, seeds weight/pod, and seeds yield/plant. All studied variables showed high heritability (H%) in genotypes/crosses, despite the exception of seeds weight/pod, which ranged from 29.14 in "D331" to 83.7 in F2 of Col x Com1. F2 plants and their parents' genotypes showed greater H%. Cr7 x AI developed the most H%, 99.04% for number of pods/plant. D331 x Com1 and Cr7 x AI exhibited moderate H% for fresh pod weight in F1, but all other crosses had high H%. F1 and F2 crosses yielded moderate to high GCV and PCV for number of seeds/pod. Variations in parental genotypes and crossings reflect genetic diversity and the possibility of selection. Crossing with 'AI,' and 'Com1' genotypes enhanced the performance of the other varieties, ‘Col’, 'D331' and 'Cr7’. Cr7 x Com1 and D331 x AI were selected as the most promising crosses for cowpea breeding programs.